The Role of Job Satisfaction in Mediating the Effects of Leadership and Intrinsic Motivation on Teacher Performance at SMA Negeri 1 Kuala, Langkat Regency - Ginting, Syahrizal; Anwar, Yohny; Darmilisani (International Conference Epicentrum of Economic Global Framework, 2025)
This study aims to analyze the role of job satisfaction in mediating the effects of leadership and intrinsic motivation on teacher performance at SMA Negeri 1 Kuala, Langkat Regency. This study employs a quantitative approach using a survey method. The study population consists of all 60 teachers at SMA Negeri 1 Kuala. Since the population size is less than 100, the entire population was used as the study sample. Data were collected via a questionnaire using a Likert scale. Data analysis was conducted using Partial Least Squares Structural Equation Modeling with the assistance of the SmartPLS 3.0 software. The results indicate that leadership has a positive and significant effect on teacher performance. Leadership also has a positive and significant effect on job satisfaction. Intrinsic motivation has a positive and significant effect on both teacher performance and job satisfaction. Furthermore, job satisfaction has a positive and significant effect on teacher performance. The results of the indirect effect test indicate that job satisfaction mediates the effect of leadership on teacher performance. Job satisfaction also mediates the effect of intrinsic motivation on teacher performance. These findings indicate that improvements in teacher performance are determined not only by the principal’s leadership and teachers’ intrinsic motivation but also by the job satisfaction teachers experience while carrying out their professional duties. Therefore, schools need to strengthen supportive leadership, enhance teachers’ intrinsic motivation, and foster job satisfaction so that teacher performance can improve sustainably.